Conspiracy and the Spanish Civil War : the brainwashing of Francisco Franco - Southworth, Herbert Rutledge (Routledge/Cañada Blanch studies on contemporary Spain, 2002)
Written by one of the most celebrated historians of the Spanish Civil War, this book acts as both an outstanding introduction to the vast literature of the war, and a monumental contribution to that literature.